Leadership, Education and Training for Youth in Contemporary African Union Programs - Cole, Lawalley (Afrika Tanulmányok / Hungarian Journal of African Studies, 2023)
From September 16–19, 2022, the U.N. Secretary-General Antonio Guterres hosted the Transforming Education Summit at U.N. Headquarters in New York on the margins of the U.N. General Assembly. This summit mobilized stakeholders to act and collaborate in solidarity to find solutions for transforming education by 2030. This summit’s outcomes were national and international commitments to transform education with increased public engagement and support. Before the conference, the African Union had just concluded its fourth Specialized Technical Committee on Education, Science, and Technology with the theme of utilizing education, science, technology, and innovation to foster recovery in Africa and respond to, strengthen, and build resilience in a post-COVID-19 pandemic. At the same time, there was a need to enhance the response from the science, technology, and innovation sectors. Growing globalization and faster technological progress have created many new social, economic, environmental, and COVID-19 problems. Because of this, the Coalition on Media and Education for Development Africa Forum (CAFOR) and its partners have been looking at the needs and opportunities that come from these changes. CAFOR and its partners are also determined to look beyond Africa’s Continental Education Strategy (CESA 16–25) and examine how schools can prepare children in Africa for jobs and technologies that have yet to be created to solve future problems with innovation. CAFOR is forwardlooking and works towards building stronger partnerships on the continent, ensuring a shared responsibility to identify new opportunities and solutions.